(untitled) (Global Journal of Medical Research, 2015)
Introduction-Antiplatelet therapy comprises a group of drugs used in the treatment of valvular heart disease, cardiac stents, rhythm disorders, pulmonary embolism and cerebrovascular diseases (1). The patients followed-up by regular measurement of the haemostatic parameters usually miss their follow-up visits due to the social reasons and are exposed to uncontrolled side effects of these drugs. The people admitting for the side effects of anticoagulant therapy are commonly seen in the emergency department because of the increased use of this group of drugs (2,3).